Classification of heart valve diseases using correlation analysis - Mohd Zubir, Suboh; Mohd Yusoff, Mashor; Abdul Rahman, Mohd Saad; M.S., Mohamed (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org